Analysis of Vibration Characteristic of Radial Permanent Magnet Coupling Under Installation Error - Jie Tian; Yanlei Xu (Jixie chuandong, 2020)
The radial permanent magnet coupling has the characteristics of high transmission efficiency， environment protection and easy assembly， due to the disconnection of the main and follower rotors， errors easily occur in the manufacturing and installation process， which affects the stability of the structure and causes the problem of vibration of the radial axis. Because of the complexity of the expression of magnetic force， it is difficult to solve by analytical mechanics. For this， the Lagrange equation of dissipative system is used to establish its dynamics equation from the angle of energy， and the bifurcation diagram of the system varying with the error value and displacement response diagram with different error values are obtained by solving it according to the actual parameters. The installation accuracy of the stable transmission of the system is obtained， meanwhile， the feasibility of the established dynamics model is also verified.